Evaluation of knowledge regarding gestational diabetes mellitus and its association with glycaemic control among gdm participants at O&G ward, Hospital USM - Ern, Huang Tze (2021)
A well-controlled glycaemic level in Gestational Diabetes Mellitus (GDM) will prevent unfavourable outcomes to the mother and child. An individual with adequate knowledge about GDM will has better glycaemic control. The aim of the study was to investigate the association between the extent of knowledge regarding GDM and glycaemic control in GDM participants. A cross sectional study was conducted on 113 GDM participants in the Obstetrics and Gynaecology (O&G) Ward in Hospital USM from April to June 2021. The GDM Knowledge Questionnaires (GDMKQ) was distributed to the participants with guidance and the most recent 1-day 4-times-a-day (QID) daily glucose were taken from participants’ medical folder. After that, the mean daily glucose was counted. A total mean knowledge score of 113 participants was 12.02 ± 1.81 and total mean daily glucose value was 5.22 ± 0.64 mmol/L. Among five knowledge domains, highest mean score was seen for knowledge regarding diet/food values domain (2.89 ± 0.40) and lowest for risk factor of GDM (1.95 ± 0.77). The present study revealed that there is no significant association between the degree of knowledge and glycaemic control (p = 0.515). It is suggested that further study should be conducted to elucidate other possible determinants of poor glycaemic control, so that a clearer understanding of modifiable antecedents of GDM-related complications can be achieved and to avoid unfavourable outcomes in GDM.